Comparison of clinic-radiological and functional outcome of intra articular distal end radius fractures managed by volar locking plate versus external fixation - Singh, Pankaj Vir; Singh, Gagandeep; Singh, Tejpal; Ghani, Abdul; Lone, Zubair A. (International Journal of Research in Medical Sciences, 2021)
Background: Distal end radius (DER) fractures are most common fractures in upper limb. Intra articular fractures can be managed either by open reduction and internal fixation by volar locking plate or can be managed by closed reduction and external fixator application or by percutaneous pinning. The purpose of our study was to compare the functional outcome of volar locking plate with that of external fixation. Methods: A prospective cohort study was conducted between June 2019 to June 2020 in Government Medical College, Jammu on 46 patients with intra articular distal end radius fractures. Of which 26 were managed by volar locking plate and 20 were managed by external fixator. the results of both groups were compared on the basis of radiological parameter and range of motion achieved post operatively. The functional outcome was evaluated using DASH score and Gartland–Werley scale. Results: Final range of motion, grip strength were better in patients managed with volar locking plate (VLP) as compared to those who were managed with external fixator (EF). Radiographically, volar tilt, radial height were all better in VLP group than EF. Conclusions: We concluded that VLP is superior method to maintain reduction till the union occurs and prevents the fracture collapse in intra articular distal end radius fractures as compared with external fixator. Thus, giving better functional and radiological outcome than the external fixator.